A dual-arm manipulation strategy using position/force errors and Kalman filter. (February 2022) - Yang, Wu-Te; Chen, Bo-Hsun; Lin, Pei-Chun
This paper presents a new coordination manipulation strategy for a custom-made dual-arm robot. With master and slave coordination infrastructure, both spatial relation and sense of touch are considered to hold an object stably. Given the known trajectory of the master arm, the slave arm fuses position and force commands by using the Kalman filter to yield optimal compensation amounts. The proposed strategy has been experimentally evaluated, and the results confirm that it was capable of dealing with fragile and flexible objects. In addition, the influence of the loop time of the digital controller on force control for this task was also investigated in mathematical and simulated ways. Furthermore, a series of experiments were designed to explore the effects that have influences on errors in force control. The main factors that affect force control error were analyzed.